2 + 3 +…+ m = (m+1) + (m+2) +…+ n —- (Part 2)

 

2 \; + \; ... \; + \; m \; = \; (m + 1) \; + \; (m + 2) \; + \; ... \; + \; n

 
Here are the first few examples:
 

2+3+..+7 = 27 = 8+9+10

2+3+4+..+43 = 945 = 44+45+46+...+61

2+3+4+..+253 = 32130 = 254+255+256+...+358

2+3+4+..+1477 = 1091502 = 1478+1479+1480+...+2089

2+3+4+..+8611 = 37078965 = 8612+8613+8614+...+12178

2+3+4+..+50191 = 1259593335 = 50192+50193+50194+...+70981

2+3+4+..+292537 = 42789094452 = 292538+292539+292540+...+413710

2+3+4+..+1705033
    = 1453569618060 = 1705034+1705035+1705036+...+2411281

2+3+4+..+9937663
    = 49378577919615 = 9937664+9937665+9937666+...+14053978

 
 
 

 
 
 
 
 
 
 
 
 
 
 
 
 
 

Advertisements

About benvitalis

math grad - Interest: Number theory
This entry was posted in Number Puzzles and tagged . Bookmark the permalink.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s